A real-world study on the safety profile of extended-interval dosing of immune checkpoint inhibitors for melanoma: a single-center analysis in Japan - Ito, Takamichi; Kaku-Ito, Yumiko; Ohno, Fumitaka; Nakahara, Takeshi (Frontiers in Medicine, 2023)
Background: Anti-programmed death-1 (PD-1) antibodies are the mainstay for the treatment of unresectable or high-risk melanoma. However, real-world data on the safety profile of their extended-interval doses (EDs) are limited, particularly in Asian patients with melanoma. Materials and Methods: In this single-center retrospective study, we analyzed the risks of immune-related adverse events (irAEs) among 71 Japanese patients (36 males; mean age, 65.0 years) who received anti-PD-1 monotherapy for melanoma at our institute. Patients who were administered ipilimumab prior to anti-PD-1 monotherapy were excluded. Patients were divided into three groups: canonical-interval dose (CD) group (n = 50, body weight-based dosing or 240 mg Q2W for nivolumab and body weight-based dosing or 200 mg Q3W for pembrolizumab), ED group (n = 14, 480 mg Q4W for nivolumab and 400 mg Q6W for pembrolizumab), and doseswitch (DS) group (n = 7, upfront CD followed by ED). Results: The CD group received nivolumab more frequently in the metastatic setting. There were no significant differences in baseline characteristics among the three groups, including in sex, age, primary tumor site, tumor subtype, and follow-up period. irAEs occurred in 36.6% (26 patients) of all patients (32.0% of the CD group, 35.7% of the ED group, and 71.4% of the DS group), while severe (grade ≥ 3) irAEs occurred in only two patients, both of whom were in the CD group. Most of the irAEs occurred during the first 6 months of anti-PD-1 therapy and, interestingly, all of the irAEs in the DS group occurred before the switch (during the CD). There was no significant difference among the three groups in the probability of irAE estimated by the Kaplan-Meier method. Conclusions: These findings may highlight the safety of ED of anti-PD-1 monotherapy in the treatment of Asian patients with melanoma.